Infectious Salmon Anemia - Iowa State University Center for Food Security and Public Health (Iowa State University Digital Repository, 2010)
Infectious salmon anemia (ISA) is one of the most important viral diseases of farmed Atlantic salmon. This highly contagious disease can be insidious, with an initially low mortality rate; however, the cumulative mortality can sometimes exceed 90% if the disease remains unchecked. Infectious salmon anemia was first described in Norway in 1984, and it continues to be a problem in that country despite control measures. Since the late 1990s, outbreaks have also been reported in other locations. This disease devastated the salmon industry of the Faroe Islands in 2000, and an epizootic in Scotland in 1998-1999 cost an estimated $32 million (U.S.) to eradicate. ISA has been a recurring problem in Chile, the Cobscook Bay in Maine, and the Bay of Fundy in New Brunswick, Canada. In New Brunswick, it results in annual losses of approximately $4.8–$5.5 million (U.S) to farmers, and millions of fish have been culled in control efforts. New outbreaks can also occur in areas where this disease was absent for many years. In 2009, an outbreak was reported again in Scotland. Understanding of the epidemiology of ISA is still incomplete, which complicates its control. The reservoirs for the virus are not known, but experiments have shown that several species of salmonids can carry virulent ISA viruses asymptomatically. These viruses might cause outbreaks if they are transmitted to farmed Atlantic salmon. Noncultivable, apparently nonpathogenic, isolates have also been detected in wild salmonids. Small changes in these viruses, analogous to the mutations that allow low pathogenicity avian influenza viruses to become highly pathogenic, may allow them to become more virulent. Some evidence suggests that certain ISA viruses may cause illness in species other than Atlantic salmon. One virus was isolated from sick farmed Pacific coho salmon in Chile in 1999, and a highly virulent strain can cause disease in experimentally infected rainbow trout.